Lawyers at work - Cosslett, Clare (Apress ; Distributed to the Book trade worldwide by Springer, 2012)
"With probing questions and articulate answers, Cosslett and her subjects shed light on the challenges of legal practice in the current legal market." BLS Law Notes, 11.16.12 Lawyers at Work reveals what it means and what it takes to be a satisfied, sane, and successful lawyer in today?s tough legal marketplace. Through incisive in-depth interviews, a top legal headhunter gives the 3rd degree to 15 successful lawyers who run the gamut of the legal profession. Practice areas represented in these profiles range from employment discrimination to corporate defense, from federal white collar prosecution to the legal structuring of complex derivative instruments, from antitrust in DC to trusts & estates in Florida, from divorce in New York to international mergers in Paris, from intellectual property in Silicon Valley to creeping expropriation in India, and from entertainment law in Hollywood to welfare rights in the Bronx. Law firm sizes range from one of the biggest in the world with over two thousand lawyers to a one-lawyer general practice. Career levels range from biglaw partners and courtroom superstars to mid-level associates and ex-lawyers. Though many of the interviewees in Lawyers at Work are generic adversaries, the interviewer brings out commonalities in their ways of working, methods of reasoning, and sources of personal motivation. Readers hear from the practitioner?s own unbuttoned lips about their career formation, daily work grind, victories and setbacks, guiding principles, professional rewards, and practical advice for aspiring lawyers